9 1 ( 1 0 1 + 1 0 2 1 + 1 0 3 1 + 1 0 4 1 + . . . )
Do NOT use a calculator! There is a better way to do this than use formulae.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
very good method. A geometric progression is the best way to approach this, but if someone had no knowledge about geometric progressions, how would they do this?
Log in to reply
They would just use Edwin Gray's solution like me. That solution would also be easier for lazy peeps like me who don't like infinite series sometimes lol
chew, nice solution, but as the proposer says, there is a better way to do this problem than by using formulae. Ed Gray
Log in to reply
The same person commented that it is the best method (see below).
OK. I will change it
We note that 1/10 = .1, 1/100 = .01, 1/1000 = .001, so adding all the terms gives .1111111111111...…… which we recognize as 1/9. Multiplying by 1/9, we get 1/81. Ed Gray
Instead of the geometric progression technique (which I would recommend if you know how to use it), we can use the fact that our numbering system is base 10. 1 0 1 + 1 0 2 1 + 1 0 3 1 + ⋯ = 0 . 1 + 0 . 0 1 + 0 . 0 0 1 + ⋯ and this converges to 0 . 1 1 1 . Furthermore, we know that 0 . 1 1 1 is just 9 1 . So we get 9 1 ⋅ 9 1 = 8 1 1 .
(
1
/
9
)
(
a
(
1
−
r
2
)
/
(
1
−
r
)
)
With a being 1/10(lim 1->3) and r being 1/10,
It equals 1/9. Then 1/9*1/9=1/9^2=1/81.
Lol that's literally using the formula for infinite geometric series. I asked not to use that formula😂
Problem Loading...
Note Loading...
Set Loading...
S = 9 1 ( 1 0 1 + 1 0 2 1 + 1 0 3 1 + 1 0 4 1 + ⋯ ) = 9 0 1 ( 1 + 1 0 1 + 1 0 2 1 + 1 0 3 1 + ⋯ ) = 9 0 1 × 1 − 1 0 1 1 = 9 0 1 × 9 1 0 = 8 1 1 An infinite geometric progression
Alternative method:
S = 9 1 ( 1 0 1 + 1 0 2 1 + 1 0 3 1 + 1 0 4 1 + ⋯ ) = 9 1 ( 0 . 1 + 0 . 0 1 + 0 . 0 0 1 + 0 . 0 0 0 1 + ⋯ ) = 9 1 × 0 . 1 1 1 1 … = 9 1 × 9 1 = 8 1 1